Orthodontic management of severe inversely impacted maxillary central incisors: a case series - Yuriko Maruya; Ryoko Hino; Manami Tadano; Seira Hoshikawa; Shinji Otake; Yuta Chiba; Kan Saito (Frontiers Media S.A., 2024)
BackgroundAbnormal positioning and dislocation of the central incisor can disturb tooth eruption. Generally, inversely impacted maxillary central incisors do not erupt naturally. Performing traction and applied extrusion of an inversely impacted maxillary central incisor with a high inclination angle of the crown is challenging. This study aimed to examine the possibility of orthodontic treatment for severely inversely impacted maxillary central incisors in a series of case studies.MethodsThe inclination angle of the tooth crown, curvature of the tooth root, and length of the formed tooth root were measured using radiography. The teeth were then fenestrated and traction was applied using a lingual arch appliance with elastics.ResultsThe average crown axis inclination was 113°, the degree of root curvature was 97.3°, and the root formation was 36.1%. Although the crown axis inclination and root curvature were severe, all the incisors were aligned in the correct position as vital teeth through surgical and orthodontic treatments.ConclusionsTraction should be performed in the early period of incisor development when root formation is not progressing, regardless of the tooth angle.